Passive Infrared (PIR) Sensor Based on Arduino in Rice Pest Repellent Device Based on Classic Life Cycle Method - Nurkhalik Wahdanial Asbara; Vera Alviani (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
The research aims to design a system to repel rice pests in rice fields by moving the scarecrow using a servo motor while sounding the speaker according to the infrared signal detection from the PIR sensor. The research method used is the waterfall method, and the research implementation time is approximately three months, starting from the proposal seminar. The rice pest repellent test was carried out by testing the reading of the infrared signal received by the PIR sensor, then moving the servo and turning on the speaker to repel bird pests in the rice fields